Pengembangan Desa Wisata Berbasis Kearifan Lokal di Desa Bawomataluo, Kecamatan Fanayama, Nias Selatan - Albertoras Telaumbanua; Asima Yanti Siahaan; Muryanto Amin (Universitas Medan Area, 2023)
The Bawomataluo Village area, Fanayama District, South Nias Regency, in addition to having beautiful natural tourism potential, also has very interesting and unique local cultural wisdom tourism potential that is still maintained. The development of a tourism village based on local wisdom is a strategic effort in maintaining the integrity of the local culture of the community and building the community. The purpose of this study is to analyze and describe the development of tourism villages based on local wisdom in accordance with tourism criteria in the Bawomataluo area as well as an overview of tourism potential, infrastructure, access, environment, community conditions, management, socio-culture and local wisdom of the community as well as analysis of supporting factors for tourism development. The study used a qualitative descriptive method by describing and interpreting all data and information obtained in the field. The results showed the development of the Bawomataluo area based on local wisdom where the important role of Si'ulu and Si'ila traditional leaders as a form of developing local wisdom in development, the role of customary norms and humum (Fondrako), and the contribution of the use of regional languages (Li Niha) in the development of the Bawomataluo area